Causal association between obstructive sleep apnea and amyotrophic lateral sclerosis: a Mendelian randomization study - Du, Rongrong; Zhu, Yahui; Chen, Peng; Li, Mao; Zhang, Ying; Huang, Xusheng (Frontiers in Aging Neuroscience, 2024)
Background: Obstructive sleep apnea (OSA) had a high prevalence in the population. Whether OSA increases the risk of amyotrophic lateral sclerosis (ALS) is unknown. Our aim was to clarify this issue using two-sample Mendelian randomization (MR) analysis in a large cohort.Methods: Two-sample MR was used to evaluate the potential causality between OSA and ALS by selecting single-nucleotide polymorphisms (SNPs) as instrumental variables (IVs) from genomewide association studies (GWAS). The inverse-variance weighted (IVW) method was chosen as the primary method to estimate causal association. Weighted median, weighted mode and simple mode methods were used as sensitivity analyses to ensure the robustness of the results.In MR analysis, IVW mode showed genetic liability to OSA was found to be significantly associated with a higher ALS risk (OR, 1.220; 95% confidence interval, 1.031-1.443; P = 0.021). No evidence of heterogeneity and horizontal pleiotropy were suggested. Conclusions: We found potential evidence for a causal effect of OSA on an increased risk of ALS.